Heparin-functionalized Pluronic nanoparticles to enhance the antitumor efficacy of sorafenib in gastric cancers. (20th January 2016) - Yang, Ying-Chi; Cai, Jun; Yin, Jie; Zhang, Jun; Wang, Kang-Li; Zhang, Zhong-Tao
Highlights: Chitosan/heparin immobilized Pluronic NP was formulated to deliver sorafenib (SRF). SRF NP induced a remarkable apoptosis of cancer cells and exhibited a marked G2/M phase cell cycle arrest. SRF NP exhibited a strong band for caspase-3 and P-53 than compared to free SRF in MGC-823 cancer cells. The heparin-functionalized NP enhanced the antitumor efficacy of SRF in gastric cancers. Abstract: In this study, chitosan/heparin immobilized delivery system was developed for the delivery of sorafenib in gastric cancers. The SRF NP was nanosized with spherical outfit and present in the amorphous form. The SRF NP exhibited a sustained release of drug at pH 7.4 conditions and enhanced drug released at pH 5.5 conditions. Flow cytometer analysis showed that cellular uptake of NP increased two-fold after 4 h of incubation compared to 1 h incubation. The SRF NP showed superior anticancer effect compared to that of free SRF in BGC-823 cancer cells. SRF NP induced a remarkable apoptosis of cancer cells consistent with the cytotoxicity assay. Approximately, ∼50% of cell fractions were observed in early apoptosis phase with ∼15% of cells in the late apoptosis stage. Consistently, SRF NP exhibited a strong band for caspase-3 and P-53 than compared to free SRF in MGC-823 cancer cells. Importantly, SRF NP showed superior anticancer effect in xenograft tumor model making it a promising delivery vehicle in the treatment of gastric cancers.